The Association Between Fasting Blood Sugar and Index of Nutritional Quality in Adult Women - Alami, Farkhondeh; Mohseni, Golsa Khalatbari; Ahmadzadeh, Mina; Vahid, Farhad; Gholamalizadeh, Maryam; Masoumvand, Mohammad; Shekari, Soheila; Alizadeh, Atiyeh; Shafaei, Hanieh; Doaei, Saeid (Frontiers in Nutrition, 2022)
Aim: It's unclear whether diet quality affects glycemic management. The index of nutritional quality (INQ) can examine diets both quantitatively and qualitatively. (INQ). Hence, this study aimed to determine whether INQ and fasting blood sugar (FBS) are related among Iranian women. Methods: This cross-sectional study was conducted on 360 adult Iranian women. Data were collected on the participants' general characteristics, medical history, anthropometric indices, physical activity, and dietary intake. For nutrient intake assessment, a valid food frequency questionnaire (FFQ) was used, and INQ was then calculated using the daily nutrient intake. Results: After adjusting for age, FBS was significantly inverse associated with INQ for vitamins A (B=-0.193, p<0.01), magnesium (B=-0.137, p<0.01), phosphor (B=-0.175, p<0.01), zinc (B=-0.113, p<0.01), vitamin K (B=-0.197, p<0.01), manganese (B=-0.111, p <0.01) and selenium (B=-0.123, p <0.01). The association between FBS and INQ for Se and Mn was disappeared after further adjustment for gender, body mass index (BMI), menopausal status, and total energy intake. Conclusion: There was a significant inverse relationship between FBS and the INQ of vitamin A, manganese, phosphor, zinc, vitamin K, magnesium, and selenium. Prospective cohort studies should be conducted to establish a causal relationship between FBS and INQ.